Perspectives of Pakistani Special Education Teachers on the Integration of Artificial Intelligence in Resource-Constrained Environments: A Qualitative Study - Hussain, Mehtab (Social Science Review Archives, 2025)
Artificial intelligence (AI) has revolutionized teaching, especially in special education, where students need personalized support and flexible methods. AI-based educational technologies are becoming more popular day by day. But many educational systems are not using such technologies, especially in low-resource contexts. This study was conducted to examine the perspective of Pakistani special-education teachers on integration of AI into a special-education classroom in resource-constrained environment. 21 purposively-selected public-school special-education teachers participated in qualitative semi-structured interviews. Braun and Clarke's (2006) thematic analysis was used to analyze the interview data. The findings of the study revealed the perspective of special-education teachers on the integration of AI into resource-constraint special-education classroom through four themes (1) readiness for AI adoption, (2) opportunities for improving special education, (3) challenges in implementation, and (4) recommendations for successful integration. The study suggests teacher training, improved technological infrastructure, and supportive policies to enable effective AI integration in special education. These findings contribute to discussions about using AI in education fairly and inclusively, especially in low-resource settings.